Spectral temporal mapping parameters of ventricular complex during antianginal therapy - Kh. Kh. Shugushev; A. B. Khadzugov; L. S. Eneeva (Российский кардиологический журнал)
The study was devoted to parametes of spectral temporal mapping of ventricular complex in coronary heart disease patients taking antianginal drugs of main classes. Eighty patients with stable angina of various functional classes were examined. Parameters of SAECG were registered with computer cardiograph, by standard methodics. All participants were divided into three groups: those taking nitrosorbide, monocinque, and atenolol. Spectral analisis of ECG gives an opportunity to detect local fluctuations of a fixed frequency, which could be used as markers of myocardial electric instability.